Injury Patterns and Emergency Care in Road Traffic Accidents in Accra - Aggrey-Orleans, J. (University of Ghana, 2019)
Road traffic accidents are a major source of morbidity and mortality in Ghana. Information on the care given to casualties and the burden of injury associated with RTAs in Ghana is inadequate. This information is needed to guide clinicians and policy makers. This study sought to examine the emergency care; injuries sustained and the socio-demographic profile of RTA casualties. This study was a cross-sectional study of all RTA casualties in 37 Military Hospital from March 2018 to March 2019. The results showed that: most RTA victims were male (66.05%), 53.95 % within 25-44 years, 54.88% were employed in blue collar jobs and 60.47% paid cash for their hospital bills. A majority (87.01%) had x-rays and laboratory investigations done in the first 48 hrs at the A&E. Orthopaedic surgeons managed 56.34% of the casualties and Neurosurgeons 21%. There were 44.67% of lower limb injuries, 23.74% upper limb injury and 13.48% head injury with 20% having multiple injuries. The highest incidence of RTAs were in vehicle occupants (35.12%), then, 30.93% in motorcycle users and 25.34% for pedestrians. A significant association was found between the following injuries and the type of RTA: head injury; chest injury; abdominal injury; lower limb injuries and soft tissue contusion. It was not so for: pelvic, spine and upper limb injuries. There was a significant association between motorcycle injury with age and sex of casualties (p< 0.001) for both. In conclusion is was evident that, the emergency care of casualties was satisfactory. Orthopeadic surgeons were essential in the trauma care. Injury patterns significantly differed across different types of accidents which could be used to help profile trauma patients. The socio-demographic profile of motorcycle related RTAs showed working age (25-45 years) males with no special trend in their occupation thus helping to know how to target preventive measures.
MPH
Keywords: Road traffic accidents; Injury; Trauma; Motorcycle